Mencegah Generasi Muda Terlibat Narkoba Melalui Pemberdayaan Institusi Lokal di Nagari Mandeh Kecamatan XI Koto Tarusan Kabupaten Pesisir Selatan - Dwiyanti Hanandini; Indraddin Indraddin; Wahyu Pramono; Nini Anggraini (Warta Pengabdian Andalas, 2019)
To be able to be the last stronghold in preventing and overcoming drug abuse, all local institutions need to be empowered. Through the empowerment of local institutions, it is expected to be able to identify the signs of children involved in drug abuse so that it can be easier to prevent and overcome them. Community service is carried out using the Lecture method and Focus Group Discussion (FGD). The targets and targets of this activity are the board of the Community Empowerment Institution (LPM) of the Nagari Indigenous Density (KAN), Bundo Kanduang, Youth Organizations, Nagari Apparatus, Nagari Deliberation Board. The activity was carried out in Nagari Mandeh, District XI Koto Tarusan, Pesisir Selatan Regency on September 1, 2019. The results of the activity could increase the knowledge of the management of local institutions in identifying drug addicts and awareness of the importance of administrators of local institutions to help prevent drug abuse in Nagari Mandeh.